EFFECT OF SALICYLIC AND HUMIC ACID ON VINCRISTINE AND N, P, K CONTENT IN MADAGASCAR PERIWINKLE LEAVES - & Rabee, Jaddo (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2016)
An Experiment carried out in Al-Yarmook Area in Baghdad for the growing season 2014 to study the effects of foliar application of Salicylic acid and Humic acid on Vincristine and NPK content in Catharanthus roseus. A factorial experiment was applied including two factors according to The Complete Randomized Block Design, the first factor included four levels of salicylic acid 0, 25, 50, and 100 mg.L-1 which were represented with S0, S1, S2, and S3 sequentially, the second factor included three levels of Humic acid 0, 0.75, and 1.5 ml.L-1 and were represented with O0, O1, and O2 sequentially to make up 12 factors in total that were distributed randomly upon three replicates and each experimental unit included 8 plants. The results were analyzed using Genestat and the differences were tested according to (LSD) with a level of probability 5% and the results were as follows: Vincristine levels increased in the leaves of Catharanthus roseus as a result of foliar application of Salicylic acid and Humic as well NPK levels in leaves. Vinblastine was not detected in all treatments. The interaction effect between 100 mg.L-1 Salicylic acid and 1.5 ml.L-1Humic acid had an exceeding effect for all the studied parameters. It may be concluded that Salicylic and Humic acid may be used to increase Vincristine alkaloid content in Periwinkle plants at the levels 100 ml.L-1 and 1.5 mg.L-1 subsequently.